Extreme UV exposure of professional cyclists - Moehrle, M.; Heinrich, L.; Schmid, A.; Garbe, C. (Dermatology, 2000)
BACKGROUND: The most important risk factor for the development of melanoma and non-melanoma skin cancer is thought to be ultraviolet (UV) radiation. To date there is no quantification of the UV exposure of outdoor sports professionals training and competing at high solar UV levels. METHODS: During eight stages of the 'Tour de Suisse' cycling race, the UV exposure of 6 professional cyclists was monitored with Bacillus subtilis spore film dosimeters. RESULTS: The measurements showed a personal UV exposure between 0.2 minimal erythema dose (MED) during the prologue and 17.2 MED during a mountain stage. The mean daily personal exposure of all full stages (prologue excluded) was 8.1 MED. The personal exposure level determined during these races exceeded international exposure limits by more than 30 times. CONCLUSION: Therefore UV exposure of sports professionals should be limited by application of sun screens, protective clothing and training/competition at low insolation.